Application of the International classification of functioning, disability and health in Taiwan: victory of the medical model. Issue 7 (9th August 2017) - Chou, Yueh-Ching; Kröger, Teppo
Abstract: Since July 2012, eligibility for disability benefits and services in Taiwan has been assessed based on the International Classification of Functioning, Disability and Health. This study examines disabled people's experiences of this new assessment system: does it incorporate the social model or a multidimensional understanding of disability and assess the needs of disabled people adequately? In-depth interviews were employed with 24 disabled persons to answer these questions from the perspective of disabled people. The findings show that the new assessment model is still medicalised: social roles and social participation are not considered, the assessment process is dominated by professionals, users' perspectives are not included and only those who are assessed to have a high level of disability are satisfied with the new system while many others would prefer the old assessment system. These findings have relevance for the analysis of needs assessments of disabled people in different countries.